(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article comprehensively analyzes the importance of legal education for women and girls and the role of educational programs in this process. The authors examine the methodologies, content, and effectiveness of delivering legal knowledge within educational programs, identifying key factors in shaping the legal culture of women. The article also reviews state policies and practical measures aimed at promoting gender equality, protecting women’s legal rights, and increasing their legal literacy in society. Furthermore, it proposes ways to improve educational programs by enriching them with modern information and communication technologies. Alongside highlighting ongoing reforms and future tasks in the field of legal education, the article emphasizes the strategic significance of educational programs in strengthening the legal awareness of women and girls.